2023
DOI: 10.3390/land12020381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Governance Structure of Rural Collective Economic Organizations on Trading Efficiency of Collective Construction Land of China

Abstract: In order to enable urban economic development, the use of the right value and asset value of rural collective construction land (RCCL) is increasingly becoming apparent and this market is experiencing rapid development. However, the arrangement of the governance structure of rural shareholding cooperatives (RSCs) can seriously affect the efficiency of collective construction land market transactions, since the governance of RSCs is related to the interests of farmers. Protecting the rights and interests of far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…On the other hand, the rural sector and rural residents share the value‐added income brought by the construction land transactions in an unreasonable proportion (Deng et al., 2023; Gu et al., 2015; Wang et al., 2018; Yep & Fong, 2009; Zhang, 2018). Agricultural land is a basic production factor for farmers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the rural sector and rural residents share the value‐added income brought by the construction land transactions in an unreasonable proportion (Deng et al., 2023; Gu et al., 2015; Wang et al., 2018; Yep & Fong, 2009; Zhang, 2018). Agricultural land is a basic production factor for farmers.…”
Section: Discussionmentioning
confidence: 99%
“…How to properly compensate landless rural households is one of the major challenges for future policy. Although the corresponding policies began to support rural collectives as landowners to conduct limited construction land transactions and raise the compensation standard for land expropriation (Gao, Liu, & Chen et al., 2020), village collectives and rural residents should be allowed to be actively and freely involved in the transaction process (Deng et al., 2023), and the process should be more transparent and democratic. In government‐led land coupling projects (i.e., the government bears the main cost of land consolidation and development), village collectives and rural residents should share a fair and reasonable percentage of the net value‐added income, for example, setting a minimum percentage (such as 40%), which can be adjusted according to different regions and projects.…”
Section: Discussionmentioning
confidence: 99%
“…This gap is primarily attributed to the low incomes of rural residents, rather than the high incomes of urban residents. Additionally, it is worth noting that the disparity within the countryside is not primarily caused by wealthy farmers being excessively rich, but rather by the fact that poor farmers have very low incomes (Li, 2017;Zhu et al, 2019;Zhou et al, 2021;Peng et al, 2022a) At the same time, the rural collective economy development policy plays a crucial role in increasing farmers' income and reducing the disparity between urban and rural areas (Deng et al, 2023). Rural collective economy refers to the economic organization development form in which the collective organization and its members implement various forms of cooperation in production, supply, and marketing under the premise of rational utilization of collective resource elements.…”
Section: Introductionmentioning
confidence: 99%
“…The progress of China's rural collective economy can be divided into three stages (Deng et al, 2023), as shown in Figure 1. Prior to the reform and opening up, China's rural areas had established a traditional collective organization based on the communalization, which experienced a phase of rapid development (Hong et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, China has entered into a rapid urbanization process, converting a substantial amount of cultivated and ecological land into urban land, driving economic and social development in cities [3]. However, in some regions, the disorderly allocation of urban land has resulted in problems such as grain reduction [4], ecological degradation [5], and the low efficiency of land use [6]. These problems challenge the sustainable development of cities [7].…”
Section: Introductionmentioning
confidence: 99%